2010
DOI: 10.1017/s1751731110001011
|View full text |Cite
|
Sign up to set email alerts
|

Increasing weaning age of piglets from 4 to 7 weeks reduces stress, increases post-weaning feed intake but does not improve intestinal functionality

Abstract: This study tested the hypothesis that late weaning and the availability of creep feed during the suckling period compared with early weaning, improves feed intake, decreases stress and improves the integrity of the intestinal tract. In this study with 160 piglets of 16 litters, late weaning at 7 weeks of age was compared with early weaning at 4 weeks, with or without creep feeding during the suckling period, on post-weaning feed intake, plasma cortisol (as an indicator of stress) and plasma intestinal fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 38 publications
3
54
2
2
Order By: Relevance
“…However, handling quality did not influence piglets' growth before and after weaning, nor the post-weaning feed intake, which was low in both treatments, as usually reported for early-weaned pigs (Pajor et al, 1991;van der Meulen et al, 2010). Because treatment differences in frequency at the feeder were not associated with differences in feed intake or weight gain, we conclude that aversively handled piglets were possibly more aroused, rather than more motivated to ingest the solid feed.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, handling quality did not influence piglets' growth before and after weaning, nor the post-weaning feed intake, which was low in both treatments, as usually reported for early-weaned pigs (Pajor et al, 1991;van der Meulen et al, 2010). Because treatment differences in frequency at the feeder were not associated with differences in feed intake or weight gain, we conclude that aversively handled piglets were possibly more aroused, rather than more motivated to ingest the solid feed.…”
Section: Discussionsupporting
confidence: 56%
“…Early-weaned piglets usually display behavioural responses indicative of distress, such as increased frequency of vocalisations (Weary et al, 1999;Colson et al, 2006), abnormal behaviours (Gonyou et al, 1998;Weary et al, 1999;Worobec et al, 1999), aggression (Jarvis et al, 2008;Devillers and Farmer, 2009), escape attempts (Worobec et al, 1999;Hö tzel et al, 2010) and low-feed intake (Gonyou et al, 1998;Van der Meulen et al, 2010), which is accompanied by impaired intestinal integrity and functionality, growth depression, increased susceptibility to disease and mortality (Pluske et al, 1997;Van der Meulen et al, 2010). These responses are attributed to the early and abrupt separation from the dam and change in diet, although it is recognised that pre-and post-weaning environmental stressors may also contribute (Weary et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In saying this, however, given IS piglets did not experience a growth check over the weaning period, one could assume that IS piglets were more familiar with the weaning process and were perhaps less stressed, although the neuroendocrine data from this experiment does not support this assumption, possibly due to sampling time and additional procedures. When IS is combined with an extended lactation, however, recovery is much quicker as evidenced by the IS35 group’s ADG results, but caution must be used to attribute the beneficial effects of the longer IS treatment, since an older weaning age per se has also been shown to improve post-weaning performance [7]. In the current study, due to the lack of a non-IS group weaned at 35 days, the effect of age and IS in the IS35 group performance cannot be separated.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing weaning age (five to seven weeks) improves GIT structure [6], increases post-weaning feed intake [7] and reduces stress [7]. However, an extended lactation causes fewer litters per sow per year and may impact production in the breeding herd [8].…”
Section: Introductionmentioning
confidence: 99%
“…During post-transport, the concentrations of CK and urea reached the upper limit or were slightly above the normal range, though AST was within the normal range for weaned piglets. In these circumstances, muscle fibres release CK and AST into the bloodstream in response to exercise or tissue damage; thus, their presence is a good marker of muscle activity or of tissue damage in pigs (Fabrega et al 2002;Yu et al 2009;van der Meulen et al 2010). In another study, Sutherland et al (2009b) found high concentrations of total proteins and albumin, suggesting that the pigs suffered mild dehydration as a consequence of transport.…”
Section: Loading Densitymentioning
confidence: 99%